2021
DOI: 10.1016/j.arrct.2021.100137
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Vitamin D Deficiency in Acute Rehabilitation Patients

Abstract: Objective To determine the prevalence of low vitamin D (<30 ng/mL), including vitamin D insufficiency (20-29.9 ng/mL) and deficiency (<20 ng/mL), in an acute rehabilitation setting. Design Cross-sectional, retrospective cohort study. Setting University-affiliated inpatient rehabilitation facility (IRF) at a metropolitan county hospital. Participants Patients (N=100; 64 men/36 women), aged 19-92 years (mean, 62±18.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent study found low (<30 ng/mL) vitamin D levels in 76% of patients in an inpatient rehabilitation facility, with diagnoses including neurologic injury and polytrauma [58]. Vitamin D and its active metabolite (1,25-dihydroxycholecalciferol) calcitriol are well documented to increase calcium and phosphate absorption in the gastrointestinal tract, increase calcium reabsorption by the kidney, and both have osteoblastogenic and osteoclastogenic effects on bone [59].…”
Section: Pathophysiologymentioning
confidence: 99%
“…A recent study found low (<30 ng/mL) vitamin D levels in 76% of patients in an inpatient rehabilitation facility, with diagnoses including neurologic injury and polytrauma [58]. Vitamin D and its active metabolite (1,25-dihydroxycholecalciferol) calcitriol are well documented to increase calcium and phosphate absorption in the gastrointestinal tract, increase calcium reabsorption by the kidney, and both have osteoblastogenic and osteoclastogenic effects on bone [59].…”
Section: Pathophysiologymentioning
confidence: 99%